Multiple and Variable NHEJ-Like Genes Are Involved in Resistance to DNA Damage in Streptomyces ambofaciens - Hoff, Grégory; Bertrand, Claire; Zhang, Lingli; Piotrowski, Emilie; Chipot, Ludovic; Bontemps, Cyril; Confalonieri, Fabrice; McGovern, Stephen; Lecointe, François; Thibessard, Annabelle; Leblond, Pierre (Frontiers in Microbiology, 2016)
Non homologous end-joining (NHEJ) is a double strand break (DSB) repair pathway which does not require any homologous template and can ligate two DNA ends together. The basic bacterial NHEJ machinery involves two partners: the Ku protein, a DNA end binding protein for DSB recognition and the multifunctional LigD protein composed a ligase, a nuclease and a polymerase domain, for end processing and ligation of the broken ends. In silico analyses performed in the 38 sequenced genomes of Streptomyces species revealed the existence of a large panel of NHEJ-like genes. Indeed, ku genes or ligD domain homologues are scattered throughout the genome in multiple copies and can be distinguished in two categories: the “core” NHEJ gene set constituted of conserved loci and the “variable” NHEJ gene set constituted of NHEJ-like genes present in only a part of the species. In Streptomyces ambofaciens ATCC 23877, not only the deletion of “core” genes but also that of “variable” genes led to an increased sensitivity to DNA damage induced by electron beam irradiation. Multiple mutants of ku, ligase or polymerase encoding genes showed an aggravated phenotype compared to single mutants. Biochemical assays revealed the ability of Ku-like proteins to protect and to stimulate ligation of DNA ends. RT-qPCR and GFP fusion experiments suggested that ku-like genes show a growth phase dependent expression profile consistent with their involvement in DNA repair during spores formation and/or germination.